A viral video and pet lemurs on Twitter. - Tara A Clarke; Kim E Reuter; Marni LaFleur; Melissa S Schaefer (PLoS ONE, 2019)
Content shared on social media platforms can impact public perceptions of wildlife. These perceptions, which are in part shaped by context (e.g. non-naturalistic setting, presence of a human), can influence people's desires to interact with or acquire wild animals as pets. However, few studies have examined whether this holds true for wild animals featured in viral videos. This study reports on opportunistic data collected on Twitter before, during, and after a video that featured a habituated ring-tailed lemur (Lemur catta), called "Sefo", in southern Madagascar went 'viral' (i.e. circulated rapidly on the internet). Our dataset of 13,953 tweets (from an 18.5-week time period in early 2016) referencing lemurs was collected using targeted keywords on the Twitonomy Service. We identified 613 individual tweets about people wanting a lemur as a pet. In addition, 744 tweets that were captured in our dataset linked to the Sefo viral video. We found that as the number of tweets about the viral video increased, so did the number of tweets where an individual wanted to have a lemur as a pet. Most tweets (91%) did not make reference to a specific species of lemur, but when they did, they often (82%) referenced ring-tailed lemurs (L. catta), ruffed lemurs (Varecia spp.), and mouse lemurs (Microcebus spp.). This study serves as a case study to consider how viral content can impact how wild animals are perceived. We close by noting that social media sites like Twitter, which are increasingly providing their users with news and information, should carefully consider how information about wild animals is shared on their platforms, as it may impact animal welfare.